SUDDEN DEATH OF AN ATHLETE: QUESTION OF ETHICS? (Fiep Bulletin - online, 2014)
The crisis of ethics and moral in human relations brought by the social-scientific-technological development, which had modified the universal values, persists until today and influences the attitude of men. The current process of the crisis of reason with ethical dilemmas raised the necessity of changes in social values, among them ethics in health. Bioethics was generated as a new dimension, for reflections upon the tension between the science of health and ethics. Guiding this process some documents were elaborated based on the Declaration of the Rights of man, the Declaration of Helsinki and the Resolution 196/96, this latter serving as the basis for the codes of ethics of the health professionals in Brazil. The values in common are the rights for freedom, safety, health and life. In relation to health and life, there is an event worrying the authorities of Medicine of Sports, the sudden death of athletes, which ratios are increasing in number. Having as base the codes of ethics for the health professionals, including Physical Education, it is necessary a reflective study, through an axiological philosophical analytical research, on the observance of the values that permeate ethics and bioethics in sports activities. This study estimates that the behavior of the professionals of this area, mainly the professional of Physical Education, is supported by these rules, in relation to the right for health and life.
Keywords: Sports; sudden death; ethics